Boron Deficiency in Trifoliate Orange Induces Changes in Pectin Composition and Architecture of Components in Root Cell Walls - Wu, Xiuwen; Riaz, Muhammad; Yan, Lei; Du, Chenqing; Liu, Yalin; Jiang, Cuncang (Frontiers in Plant Science, 2017)
Boron (B) is a micronutrient indispensable for citrus and B deficiency causes a considerable loss of productivity and quality in China. However, studies on pectin composition and architecture of cell wall components in trifoliate orange roots under B deficiency condition are not sufficient. In this study, we investigated the alteration in pectin characteristics and the architecture of cell wall components in trifoliate orange [Poncirus trifoliata (L.) Raf.] roots under B starvation. The results showed that B-deficient roots resulted in a significant enlargement of root tips and an obvious decrease in cell wall B and uronic acid (UA) content in Na2CO3-soluble pectin compared with B-adequate roots. Meanwhile, they showed a decrease of 2-keto-3-deoxyoctanoic acid (KDO) in CDTA-soluble and Na2CO3-soluble pectin in cell walls, while the degree of methylation (DM) of CDTA-soluble pectin was significantly increased under B deficiency. Transmission electron microscope (TEM) micrographs of B deficient plants showed a distinct thickening of the cell walls, with the thickness 1.82 times greater than that of control plant roots. The results from fourier-transform infrared spectroscopy (FTIR) showed that B deficiency changed the mode of hydrogen bonding between protein and carbohydrates (cellulose and hemicellulose). The FTIR spectra exhibited a destroyed protein structure and accumulation of wax and cellulose in the cell walls under B starvation. The 13C nuclear magnetic resonance (13C-NMR) spectra showed that B starvation changed the organic carbon structure of cell walls, and enhanced the contents of amino acid, cellulose, phenols and lignin in the cell wall. The results reveal that the swelling and weakened structural integrity of cell walls, which induced by alteration on the network of pectin and cell wall components and structure in B-deficient roots, could be a major cause of occurrence of the rapid interruption of growth and significantly enlarged root tips in trifoliate orange roots under B-insufficient condition.